Realist evaluation of Schwartz rounds® for enhancing the delivery of compassionate healthcare: understanding how they work, for whom, and in what contexts - J. Maben; C. Taylor; E. Reynolds; I. McCarthy; M. Leamy (BMC Health Services Research, 2021)
Abstract Background Healthcare work is known to be stressful and challenging, and there are recognised links between the psychological health of staff and high-quality patient care. Schwartz Center Rounds® (Rounds) were developed to support healthcare staff to re-connect with their values through peer reflection, and to promote more compassionate patient care. Research to date has focussed on self-report surveys that measure satisfaction with Rounds but provide little analysis of how Rounds ‘work’ to produce their reported outcomes, how differing contexts may impact on this, nor make explicit the underlying theories in the conceptualisation and implementation of Rounds. Methods Realist evaluation methods aimed to identify how Rounds work, for whom and in what contexts to deliver outcomes. We interviewed 97 key informants: mentors, facilitators, panellists and steering group members, using framework analysis to organise and analyse our data using realist logic. We identified mechanisms by which Rounds lead to outcomes, and contextual factors that impacted on this relationship, using formal theory to explain these findings. Results Four stages of Rounds were identified. We describe how, why and for whom Schwartz Rounds work through the relationships between nine partial programme theories. These include: trust safety and containment; group interaction; counter-cultural/3rd space for staff; self-disclosure; story-telling; role modelling vulnerability; contextualising patients and staff; shining a spotlight on hidden stories and roles; and reflection and resonance. There was variability in the way Rounds were run across organisations. Attendance for some staff was difficult. Rounds is likely to be a ‘slow intervention’ the impact of which develops over time. We identified the conditions needed for Rounds to work optimally. These contextual factors influence the intensity and therefore degree to which the key ingredients of Rounds (mechanisms) are activated along a continuum, to produce outcomes. Outcomes included: greater tolerance, empathy and compassion for self and others; increased honesty, openness, and resilience; improved teamwork and organisational change. Conclusions Where optimally implemented, Rounds provide staff with a safe, reflective and confidential space to talk and support one another, the consequences of which include increased empathy and compassion for colleagues and patients, and positive changes to practice.